Lifetime commercial heterosexual behavior among HIV negative elderly men from rural Chengdu, China: a modified knowledge-attitude-practice perspective - Yi Yang (BMC, 2021)
Abstract Background China is facing big challenges to achieve the “90–90-90 targets”. The HIV prevalence of elderly (≥50 years) men have been steadily increasing in China, mainly through the sexual transmission route, but sexual behaviors of them are far from well-studied. In 2019, elderly men accounted for 59.2% of HIV/AIDS cases in Sichuan, China. Methods The research design is a cross-sectional study. Face-to-face interviews were conducted among 795 HIV negative elderly men from rural Chengdu, capital City of Sichuan. Bivariate and multivariate logistic regression models were applied to examine factors associated with commercial heterosexual behavior from a modified Knowledge-Attitude-Practice (KAP) perspective. Results 129 (16.23%) respondents admitted high-risk sexual behaviors, including 11.07% commercial heterosexual behavior, 6.16% extramarital, 2.89% casual and 0.25% homosexual behavior, and no one used condom consistently. 427(68.43%) had ever gotten HIV-related Health Education (HRHE), mainly through mass media (70.49%). The HIV-related knowledge awareness rate was only 31.41%. Migration history (AOR =2.46,95% CI = 1.02–5.91), age(≥60 vs. 50–59, OR = 0.41, 95% CI = 0.19–0.91), receiving HRHE from mass media (OR = 0.37, 95%CI = 0.16–0.85), marital status (married vs. never married, OR = 0.04, 95%CI = 0–0.52), and undecided (AOR =0.02, 95%CI = 0.01–0.09) and objection (AOR =0.04, 95%CI = 0.01–0.1) attitude toward commercial sex were related to lifetime commercial heterosexual behavior. Conclusions High-risk sexual behaviors are common among elderly men from rural areas in Chengdu. Receiving HRHE from mass media and undecided and objection attitude toward commercial sex prevent elderly from being involving in commercial heterosexual behavior. According to the results, health facilities should continue to conduct systematic interventions, paying more attention to 50–59 years old group. Sex and condom use need to be talked in public. Working with mass media, health facilities give elderly men education not only focusing on HIV/AIDS, but also on knowledge and skills of condom use.